Efficient antiproliferative and antiangiogenic effects on human ovarian cancer growth by gene transfer of attenuated mutants of Shiga- like toxin I. Issue 4 (1st July 2008) - Wei, F.; Cao, S.; Ren, X.; Liu, H.; Yu, J.; Li, H.; Hao, X.
Abstract : To evaluate the potential effect of anticancer and antiangiogenesis of Stx1 W203F and Stx1 R170H, two attenuated mutants of Shiga-like toxin I (Stx1), in cancer gene therapy. Antiproliferative effects of these Stx1 mutants were tested in human ovarian carcinoma cell line SKOV3 and human umbilical vein endothelial cells (HUVECs) in vitro . Effect of these Stx1 mutants on inducing cell death and cell cycle arrest was analyzed in SKOV3 cells. Influence of these Stx1 mutants on endothelial cell function was analyzed in HUVECs. in vivo therapeutic effect of these Stx1 mutants on SKOV3 was explored using xenograft models in nude mice. These Stx1 mutants can inhibit the growth of SKOV3 or HUVECs and this effect can be abrogated by antibody specific for Stx1. They caused considerable cell death of SKOV3 cells in 24 h; neither caspase activity nor DNA fragmentation was observed, and necrosis is the major mode of cell death. These Stx1 mutants can induce cell cycle arrest of SKOV3 cells in G2 –M or S phase depending on the dosage of gene transfer. Furthermore, they significantly decreased migration and capillary tube formation of HUVECs at low dose. in vivo study showed that Stx1 W203F but not Stx1 R170H significantly suppressed transplanted SKOV3 tumor growth in nude mice model. Interestingly, the microvessel densities of tumor treated with Stx1 W203F and Stx1 R170H were significantly reduced. This study suggests that genes encoding attenuated Stx1 can be selected as good candidates for the gene therapy of ovarian carcinoma because of their antiproliferative and antiangiogenic effects.